2000
DOI: 10.1161/01.str.31.6.1311
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion- and Perfusion-Weighted MRI

Abstract: Background and Purpose-Diffusion-weighted imaging (DWI) and perfusion-weighted imaging (PWI) have been used increasingly in recent years to evaluate acute stroke in the emergency setting. In the present study, we compared DWI and PWI findings in acute stroke patients with and without severe extracranial internal carotid artery (ICA) disease. Methods-Twenty-seven patients with nonlacunar ischemic stroke were selected for this analysis. DWI, PWI, and conventional MRI were performed in all patients within 24 hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 123 publications
(45 citation statements)
references
References 34 publications
(32 reference statements)
4
41
0
Order By: Relevance
“…Thus, multiparametric MRI of brain perfusion appears to be suitable for differentiating between delayed perfusion resulting from chronic hemodynamic impairment in the large cerebral arteries and manifest ischemia threatening brain tissue. Our findings agree with and extend an earlier study that showed that brain perfusion is delayed in the presence of occlusion of the ICA and additional arteries of the circle of Willis (19). The current evidence suggests that in chronic cerebral ischemia with recurring ischemic events over weeks the perfusion-diffusion mismatch may be as severe as in acute stroke.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, multiparametric MRI of brain perfusion appears to be suitable for differentiating between delayed perfusion resulting from chronic hemodynamic impairment in the large cerebral arteries and manifest ischemia threatening brain tissue. Our findings agree with and extend an earlier study that showed that brain perfusion is delayed in the presence of occlusion of the ICA and additional arteries of the circle of Willis (19). The current evidence suggests that in chronic cerebral ischemia with recurring ischemic events over weeks the perfusion-diffusion mismatch may be as severe as in acute stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Recent observations have shown that brain infarcts may become as large as predicted by the perfusion abnormalities in acute MR images (7,14), they may regress (15,16), or they may deteriorate despite arterial recanalization (17,18). Moreover, it is well established that chronic internal carotid artery (ICA) occlusion is accompanied by a prominent perfusion impairment in the downstream brain region (19). We encountered a number of patients who presented with recurring transient ischemic attacks and a severe perfusion-diffusion mismatch but remained clinically stable and did not develop structural brain lesions as evident from T2-weighted (T2W) images.…”
mentioning
confidence: 99%
“…According to previous studies of TTP maps in patients with high-grade ICA stenosis, vessel pathology was supposed to influence the reliability of PWI maps. 37,50 However, we found the performance of CBF MRI not related to the presence of extracranial vessel pathology because an ipsilateral stenosis or occlusion did not significantly change the C-ratio. This discrepancy to the previous studies can be explained by the fact that CBF maps are less sensitive to collateral flow than TTP maps.…”
Section: Zaro-weber Et Al Mri-cbf In Acute Stroke Compared With H 2 Omentioning
confidence: 64%
“…TTP maps without AIF have been frequently studied, because they are easy to obtain, robust, and well comparable among different imaging facilities. 8,12,37 Regarding the underlying principles, however, AIF-based maps may be superior and maps of the mean transit time or the CBF should be favored. Because MRI-based CBF was seldom used in clinical trials and because a clinically relevant volumetric approach is not yet available, our study adds important evidence to the validation of MRI-based CBF measurement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation